P507 Vulvar Crohn's disease: A challenging diagnosis. (27th May 2021) - Sahar, N; Dahmani, W; Nour, E; Aya, H; Wafa, B A; Aida, B S; Ahlem, B; Mehdi, K; Hanene, J; Ali, J
Abstract: Background: Crohn's disease is an inflammatory bowel disorder with several well-known extraintestinal manifestations, such as erythema nodosum, uveitis, and arthritis. Less commonly observed are cutaneous, so-called metastatic lesions of the vulva, which represent a diagnostic and therapeutic dilemma and require a multidisciplinary approach. The objective of this study was to report a case series of patients with vulvar Crohn's disease (VCD), describe its clinical features, histopathologic characteristics and therapeutic management. Methods: In this retrospective study, we reviewed all cases of VCD seen in our department between 2008 and 2016. Data concerning age at diagnosis of VCD, vulval symptoms at presentation, histologic findings, and different treatment modalities were recorded. Only patients with both clinical features of VCD [knife-cut fissures, edema, ulceration] and histologic confirmation were included. A total of 3 cases were identified among 106 female patients with CD. Results: Case 1: A 58-year-old patient, presented with a 4-year history of vulvar pain and itching. She had no bowel complaints. Clinical examination revealed hypertrophic exophytic lesions associated with linear ulcearations involving the vulva. A biopsy from the lesional skin showed non caseating gigantocellular granuloma. In view of the clinical and histopathological features, a diagnosis of Crohn's disease of the vulva was made. Anti TNF treatment with adalimumab was started, resulting in a significant regression of the lesions. Case 2: A 47-year-old patient presented to our department with complaints of painful, persisting vulvar ulcers, and resulting dysperunia for 2 years. On clinical examination she had unilateral vulvar oedema with multiple "knife-cut" linear ulcers. A skin biopsy was done which revealed dense inflammatory lymphocytic infiltrate with non caseating granulomas. Treatment with adalimumab was initiated. An improvement of symptoms was noted. Case 3: A 16-year-old patient with no remarkable medical history, presented with a 2-year- history of persistent cheilitis and vulvar pain. Clinical examination of the external genitalia revealed 'knife-cut' vulvar fissures with important bilateral labial swelling and multiple papules on the surrounding skin. Histological analysis showed chronic inflammatory infiltrate with noncaseating tuberculoid granulomas. Anti-TNF treatment with infliximab was started with partial regression of lesions. Conclusion: Our findings highlight the importance of keeping VCD on the differential diagnosis when faced with a range of vulvar symptoms. Anti-TNF agents seem to be an efficient treatment strategy for this particular localization.